The end of the law : mosaic covenant in Pauline theology - Meyer, Jason C (Nashville, Tenn. : B & H Academic, 2009)
Commonly understood as the first theologian of the Christian faith, Paul set forth the categories by which we describe our relationship with Christ. Did he understand the new covenant Jesus announced at the Last Supper primarily as a replacement of the old Mosaic covenant God made with Israel, or as a renewal and completion of the old? Jason Meyer surveys the various differences that have been argued between the two covenants in The End of the Law, carefully and inductively perfoming a semantic, grammatical, and contextual analysis of all the Pauline texts dealing with covenant concepts.Book seven of the New American Commentary Studies in Bible & Theology series, an extension of the long-respected New American Commentary.
Includes bibliographical references (p. [289]-317) and indexes
Keywords: Bible. -- Theology; Bible. -- Relation to Epistiles of Paul; Law (Theology) -- Biblical teaching; Grace (Theology) -- Biblical teaching; Covenants -- Biblical teaching